Toxicity of Corymbia citriodora essential oil compounds against Ascia monuste (Linnaeus, 1764) (Lepidoptera: Pieridae) and Plutella xylostella (Linnaeus, 1758) (Lepidoptera: Plutellidae) - Santos, Renata C.; Paes, Jhersyka S.; Ribeiro, Arthur V.; Santos, Abraão A.; Picanço, Marcelo C. (Entomological Communications, 2020)
Essential oils (EO’s) have been investigated as a safe alternative to pest management. The toxicity of an EO can vary due to abiotic and biotic factors. The individual compounds of different EO’s have shown promise to insect control and they may present toxicity similar to or greater than the EO’s. In this study, we determined the toxicity of Corymbia citriodora EO compounds against Ascia monuste (Linnaeus, 1764) and Plutella xylostella (Linnaeus, 1758). Citronellal, trans-caryophyllene, and citronellol (LD50 = 23.24, 24.17 and 27.84 μg/mg, respectively) were the most toxic compounds to A. monuste. On the other hand, α-pinene and β-pinene presented low toxicity to this pest. For P. xylostella, citronellol and citronellal were the most toxic compounds (LD50 = 22.36 and 25.53 μg/mg, respectively). The other compounds presented lower toxicity with similar doses. Thus, the individual compounds of C. citriodora EO can be an alternative for A. monuste and P. xylostella control.